1992
DOI: 10.1111/j.1474-8673.1992.tb00336.x
|View full text |Cite
|
Sign up to set email alerts
|

Further analysis of the inhibitory effects of dihydroergotamine, cyproheptadine and ketanserin on the responses of the rat aorta to 5‐hydroxytryptamine

Abstract: 1. The aim of the present study was to analyse the inhibitory effects of dihydroergotamine, cyproheptadine and ketanserin on the rat aorta contractile responses to 5-HT. Initially phenoxybenzamine treatment was used to determine whether spare receptors exist at the maximum responses to 5-HT. Then the reversibility of the inhibitory effects of phentolamine, dihydroergotamine, cyproheptadine and ketanserin against the fast and slow response of the rat aorta to 5-HT were determined. 2. Phenoxybenzamine caused non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…Spiperone (Cohen et al 1982) and ketanserin, which are selective 5-HT 2A -receptor antagonists, but not the selective α 1 -and α 2 -adrenoceptor antagonists, prazosin and idazoxan (Doggrell 1987), are potent inhibitors of the rat aorta serotonergic response. However, the rat aorta 5-HT 2A -receptors may be atypical as the affinity constants (K A ) for serotonin are 10-100-fold greater (Doggrell 1992(Doggrell , 1995, and this study) than those previously reported for serotonin at 5-HT 2A -receptors. K A values for serotonin in the order of 1-8i10 − 7  have been obtained at the 5-HT 2A -receptors of the rabbit aorta (Clancy & Maayani 1985 ;Leff et al 1987), calf coronary and pulmonary artery (Frenken & Kaumann 1987) and rat kidney vasculature (Bond et al 1989).…”
Section: Discussionsupporting
confidence: 44%
“…Spiperone (Cohen et al 1982) and ketanserin, which are selective 5-HT 2A -receptor antagonists, but not the selective α 1 -and α 2 -adrenoceptor antagonists, prazosin and idazoxan (Doggrell 1987), are potent inhibitors of the rat aorta serotonergic response. However, the rat aorta 5-HT 2A -receptors may be atypical as the affinity constants (K A ) for serotonin are 10-100-fold greater (Doggrell 1992(Doggrell , 1995, and this study) than those previously reported for serotonin at 5-HT 2A -receptors. K A values for serotonin in the order of 1-8i10 − 7  have been obtained at the 5-HT 2A -receptors of the rabbit aorta (Clancy & Maayani 1985 ;Leff et al 1987), calf coronary and pulmonary artery (Frenken & Kaumann 1987) and rat kidney vasculature (Bond et al 1989).…”
Section: Discussionsupporting
confidence: 44%